Humoral and cell-mediated immune responses after a booster dose of HBV vaccine in HIV-infected children, adolescents and young adults - Giacomet, Vania; Masetti, Michela; Nannini, Pilar; Forlanini, Federica; Clerici, Mario; Zuccotti, Gian Vincenzo; Trabattoni, Daria (PloS one, 2018)
HBV vaccine induces protective antibodies only in 23-56% of HIV-infected children. The aim of our study is to evaluate the immunologic effects of a booster dose of HBV vaccine in HIV-infected youth. 53 young HIV-infected patients in whom HBV vaccination did not elicit protective Ab titers were enrolled. All patients were on ART with optimal immunological and viral response. All patients received a booster dose of HBV vaccine (HBVAXPRO 10 μg i.m.). HBV-specific Ab titer, viral load and CD4+ T cells were measured at baseline (T0), T1, T6 and T12 months. In a subgroup of 16 patients HBV-specific cell mediated immune responses were evaluated at baseline, at T1 and T6. The booster dose induced seroconversion in 51% of patients at T1, 57% at T6, and49% at T12; seroconversion rate was significantly correlated with CD4+T cells at T0 and to the CD4 nadir. The booster dose induced HBV-specific cell mediated immunity at T6 mainly in Responders (Rs): Effector Memory CD8+T cells, HBV-specific TNFα-, IFNγ-, granzyme secreting CD8+ T cells and IL2-secreting CD4+ T cells were significantly increased in Rs compared to T0. In Non Responders (NRs), HBV-specific IL2-secreting CD4+ T cells, Central and Effector Memory CD8+ T cells were the only parameters modified at T6. Seroconversion induced by a booster dose of vaccine correlates with the development of T cell immunological memory in HIV-infected patients who did not respond to the standard immunization. Alternate immunization schedules need to be considered in NRs.